2022
DOI: 10.1038/s41598-022-22822-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of repurposed drugs targeting significant long non-coding RNAs in the cross-talk between diabetes mellitus and Alzheimer’s disease

Abstract: The relationship between diabetes mellitus (DM) and Alzheimer’s disease (AD) is so strong that scientists called it “brain diabetes”. According to several studies, the critical factor in this relationship is brain insulin resistance. Due to the rapid global spread of both diseases, overcoming this cross-talk has a significant impact on societies. Long non-coding RNAs (lncRNAs), on the other hand, have a substantial impact on complex diseases due to their ability to influence gene expression via a variety of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…This shows that there is an extensive reprogramming of the gene expression in S. mansoni worms that goes beyond the changes in protein-coding gene expression. Indeed, this observation is in line with previous studies showing that lncRNA levels can be modulated by drugs in S. mansoni [23] and in other eukaryotes [25,[37][38][39][40].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This shows that there is an extensive reprogramming of the gene expression in S. mansoni worms that goes beyond the changes in protein-coding gene expression. Indeed, this observation is in line with previous studies showing that lncRNA levels can be modulated by drugs in S. mansoni [23] and in other eukaryotes [25,[37][38][39][40].…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have demonstrated and validated the modulation of lncRNA levels in other eukaryotes as a response to different drugs [25,[37][38][39][40]. According to the recently published "ncRNADrug" database, a manually curated resource containing thousands of ncRNAs in current literature found to be associated with drug response and resistance [37], a set of 67 unique lncRNAs has been validated as DE under the regulation of 74 different molecules, whilst regulating the expression of 127 unique genes.…”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez et al (2021) developed a machine learning framework to predict a list of genes that associate with different stages of AD, based on gene expression data from multiple datasets, for drug repurposing. Ghiam et al (2022) 38 examined the role of long non-coding RNAs (lncRNAs) in the cross-talk between diabetes and AD using two bipartite networks, including (1) an mRNA-miRNA network with common mRNAs in diabetes and AD and (2) an miRNA-lncRNA network with high-degree miRNAs obtained from the mRNA-miRNA network. They utilized machine learning to predict the effects of drugs on the expression of high-degree lncRNAs selected from the miRNA-lncRNA network.…”
Section: Introductionmentioning
confidence: 99%